Webinar Cyber security and IR 4.0 Awareness - Mritha, Ramalingam (Faculty of Computing, 2021)
PEKAN, 22 September 2021 - A webinar on Awareness of Cyber security & Industrial Revolution 4.0 was organized by Politechnic Balik Pulau, Penang and conducted virtually through Cisco Webex and Facebook live.